1997
DOI: 10.1086/310706
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Cosmic-Ray Positron Fraction from 1 to 50 G[CLC]e[/CLC]V

Abstract: Two measurements of the cosmic-ray positron fraction as a function of energy have been made using the High Energy Antimatter Telescope (HEAT) balloon-borne instrument. The first flight took place from Ft. Sumner, New Mexico in 1994, and yielded results above the geomagnetic cutoff energy of 4.5 GeV. The second flight from Lynn Lake, Manitoba in 1995 permitted measurements over a larger energy interval, from 1 GeV to 50 GeV. In this letter we present results on the positron fraction based on data from the Lynn … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

73
397
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(472 citation statements)
references
References 14 publications
73
397
1
1
Order By: Relevance
“…Especially the PAMELA data confirm the hint of excess of positron fraction previously discovered by HEAT [7,8] and AMS [9]. Many theoretical models have been proposed to explain these phenomena in past years, among which a class of leptonic dark matter (DM) annihilation models is of particular interest (e.g., [10,11] or see the review [12]).…”
Section: Introductionsupporting
confidence: 59%
“…Especially the PAMELA data confirm the hint of excess of positron fraction previously discovered by HEAT [7,8] and AMS [9]. Many theoretical models have been proposed to explain these phenomena in past years, among which a class of leptonic dark matter (DM) annihilation models is of particular interest (e.g., [10,11] or see the review [12]).…”
Section: Introductionsupporting
confidence: 59%
“…Also shown is the e + /(e + + e − ) spectrum for the benchmark model (red curve). Although we only fit to data from PAMELA [4] we include also data from HEAT [93,94], AMS01 [95], and CAPRICE94 [96], for comparison. small window of N e values yield a good fit to both data sets.…”
Section: Jhep01(2011)064mentioning
confidence: 99%
“…A number of recent measurements of cosmic ray electrons and positrons have been interpreted as possible evidence for dark matter [1][2][3][4][5][6]. In particular, it has been suggested that the features of the e þ e À spectrum and positron fraction reported by PAMELA [1], ATIC [2], PPB-BETS [3], the Fermi Gamma Ray Space Telescope (FGST) [4], HEAT [5], and AMS-01 [6] may originate from either DM annihilations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or decays [22][23][24][25][26][27] taking place in the Galactic Halo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, decays or annihilations directly into e þ e À final states are disfavored by the observed spectra, requiring instead muon or tau final states. It has been shown that dark matter with a mass $10 [2][3][4][5] GeV that annihilates/decays into À þ , À þ , or À þ À þ can reproduce the observed cosmic ray features [11]. This results in copious production of neutrinos as the heavy leptons decays.…”
Section: Introductionmentioning
confidence: 99%